PTU-023 The use of proton pump inhibitors and clopidogrel in a district general hospital. (23rd September 2015) - Butcher, C; Butt, S K; Fuller, L; Ifijen, M; Good, B; Van Someren, N; Besherdas, K
Abstract : Introduction: Clopidogrel is an important anitiplatelet agent used to protect patients from acute coronary syndromes (ACS), cerebrovascular events (CVA) and prevent coronary stent thromboses. Patients receiving clopidogrel are commonly treated with proton pump inhibitors (PPIs) to protect from GI bleeding. Recent studies have sugessted PPIs (in particular omeprazole) which are inhibitors of cytochrome P-450, may decrease the efficacy of clopidogrel, which is metabolised to its active form by the same enzyme complex. Clinically, this is important, since the decrease in antiplatelet efficacy may be associated with an increased risk. Therefore, has been suggested that the concomitant use of PPI and clopidogrel be discouraged and other agents with no such interaction, for example, famotidine be used for GI protection. Methods: The aim was to assess the reasons for concomitant use of PPIs and clopidogrel in our hospital. This was a retrospective analysis of patients identified from May 09 to November 09 from the pharmacy JAC Medicines database with prescriptions of PPI and clopidogrel. Patients with PPI/clopidogrel therapy were scrutinised for indications of use, prescriber, and whether patients underwent foregut imaging to obtain accurate diagnosis prior to initiation of PPI. Results: 36 patients who were on PPI therapy with clopidogrel were identified from the database. There were 24 females and mean age was 75 (41–96). Of these 33/36 (92%) patients had an acute coronary event of which 7/33 (21%) had a coronary stent inserted. 3/36 (8%) patients had a CVA as indication for clopidogrel. All 33/36 (92%) patients with a diagnosis of ACS had PPI therapy started by a cardiologist. The PPI of choice was omeprazole with 20/36 (57%) with the remainder being lansoprazole 15/36 (42%) and 1/36 (1%) on nexium. 8/36 (22%) underwent endoscopy post initiation of PPI therapy. Just over half of these patients 19/36 (53%) were prescribed PPI therapy for prophylaxis against GI bleeding with the remainder being prescribed PPI for uninvestigated dyspepsia/GORD (10/36) 28%, gastric/duodenal ulceration (4/36) 11% and oesophagitis (3/36) 6%. Conclusion: This study demonstrates that despite emerging evidence and widespread publicity of the reduced efficacy of clopidogrel with PPIs, in particular omeprazole, this PPI continues to be used particularly in cardiac patients without an accurate gastrointestinal diagnosis requiring prophylaxis. Furthermore this places those patients with coronary stents at risk of thromboses. We propose that other GI protective agents, such as famotidine (for which there is evidence base) be prescribed to those patients on clopidogrel.